Simultaneous determination of seven compounds in Chinese patent medicines Chenxiangqu by matrix solid‐phase dispersion coupled with ultra high performance liquid chromatography and quadrupole time‐of‐flight mass spectrometry. Issue 14 (25th May 2020) - Chu, Chu; Zhang, Huan; Mao, Hui; Liu, Caijing; Jiang, Luyi; Lian, Linmin; Li, Jing; Zhu, Jiaming; Chen, Wei; Yan, Jizhong
Abstract: A simple, efficient, and sensitive strategy by coupling matrix solid‐phase dispersion with ultra high performance liquid chromatography quadrupole time‐of‐flight mass spectrometry was proposed to extract and determine three types of components (including seven analytes) in Chinese patent medicines Chenxiangqu. The highly ordered mesoporous material Fe‐SBA‐15 synthesized under weakly acidic conditions was selected as a dispersant in matrix solid phase dispersion extraction for the first time. Several parameters including the mass ratio of sample to dispersant, the type of dispersant, the grinding time, and the elution condition were investigated in this work. Under the optimized conditions, 20 compounds were identified by quadrupole time‐of‐flight mass spectrometry and seven analytes were quantified. The results demonstrated that the developed method has good linearity ( r  > 0.9995), and the limits of detection of the analytes were as low as 0.55 ng/mL. The recoveries of all seven analytes ranged from 97.6 to 104.6% (relative standard deviation < 3.4%). Finally, the improved method was successfully applied to determination of five batches of Chenxiangqu samples, which provided a robust method in quality control of Chinese patent medicines Chenxiangqu. The developed strategy also shows its great potential in analysis of complex matrix samples.